Neoplasms of the appendix: an experience of a tertiary hospital in Southwestern Nigeria (2020)
Background: The appendix is a vestigial tube like organ. Its exact physiological function is unknown. Appendectomies are done usually following a clinical diagnosis of acute appendicitis. Neoplasms can arise from this organ as well. Carcinoids are the most common neoplasms arising commonly at the tips. This retrospective review of neoplasms of the appendix was aimed at identifying the incidence and describing the histological variants of neoplasms of the appendix in our environment. Materials and Methods: This study was a 10 year retrospective review of all appendectomy specimens submitted to the Department of Pathology, University College Hospital, Ibadan, Nigeria, from January 1, 2009, to December 31, 2018. Microscopy was done examining the longitudinal sections from the tip to the base of the appendix. The histological diagnosis was extracted from the records in the department and classified using the WHO classification of tumors of the appendix (2019). Patients’ biodata such as age and sex were also extracted. The data were analyzed for frequency distribution using SPSS 23. Results: The incidence of neoplasms in the appendix was 0.84% of the 1071 appendectomies received in our department over the study period. Low grade appendiceal mucinous neoplasm (LAMN) was the most common histological variant accounting for 55.5% of neoplasms, followed by metastatic carcinoma at 22.2% and carcinoids at 11.1%. There was a female preponderance of 77.8%. Conclusion: Neoplasms of the appendix are rare in our environment, and LAMN was the most common neoplasm of the appendix in our institution. There is a female preponderance among patients with appendiceal neoplasms.